PENERAPAN KONSELING INDIVIDUAL PENDEKATAN PERSON CENTERED DENGAN TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KEMAMPUAN MANAJEMEN WAKTU PADA SISWA - Citra Rana Sari; Vita Apriani; Melani Putri Triana; Nia Anggraini; Evi Fitriyanti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Time management is an important skill that greatly affects students' academic achievement and personal development. Many students have difficulty managing their time effectively, which results in the habit of procrastinating, academic stress, and an imbalance between academic and non-academic activities. This study aims to explore the application of individual counseling services with a person-centered approach with self-management techniques in improving students' time management skills. The study used a qualitative descriptive method with a subject of a grade XI student of SMA Negeri 7 Jakarta who showed problems in time management. This study is an action research that examines an action that aims to provide solutions, improve abilities, quality and soon. The intervention was carried out in two cycles of individual counseling services that were designed in a structured manner. The results showed that the application of a person-centered approach with self-management techniques was effective in helping students increase self-awareness, design independent study schedules, and reduce the habit of procrastinating. Counselees showed an increase in discipline and ability to determine priorities.